2020
DOI: 10.1016/j.bcp.2019.113727
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of beta adrenoceptor-mediated myocardial contraction and calcium dynamics by the G protein-coupled estrogen receptor 1

Abstract: The G protein‐coupled estrogen receptor (GPER) participates in many cardioprotective activities. However, the mechanisms of such activities are not known. We have begun to investigate the effects of alterations in GPER activity on myocardial signaling via the beta‐1 adrenergic receptor. In freshly isolated primary murine cardiomyocytes, β1AR agonist isoproterenol triggers robust Ca2+ signals that are oscillatory and dependent on extracellular entry. GPER activation dose‐dependently inhibits the isoproterenol‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The reduction in cardiomyocyte apoptosis could probably be related to the activation of the PI3K/Akt pathway, as already shown for serum-deprived hypoxic CF incubated with G-1 [ 59 ]. Complementing the beneficial cardiac action of this receptor, GPER activation also regulates myocardial Ca 2+ dynamics, left ventricular pressure, and the frequency of ectopic contractions in isoproterenol-induced MI model in female rats and prevents potentiation of peak currents through L-type Ca 2+ channels in cardiomyocytes [ 95 ].…”
Section: Er Modulation and Mi: Preclinical Studiesmentioning
confidence: 99%
“…The reduction in cardiomyocyte apoptosis could probably be related to the activation of the PI3K/Akt pathway, as already shown for serum-deprived hypoxic CF incubated with G-1 [ 59 ]. Complementing the beneficial cardiac action of this receptor, GPER activation also regulates myocardial Ca 2+ dynamics, left ventricular pressure, and the frequency of ectopic contractions in isoproterenol-induced MI model in female rats and prevents potentiation of peak currents through L-type Ca 2+ channels in cardiomyocytes [ 95 ].…”
Section: Er Modulation and Mi: Preclinical Studiesmentioning
confidence: 99%
“…As for prevention of β adrenoceptor (βAR)-mediated potentiation of VDCE, recent evidence suggests that GPER may be an intrinsic component of β 1 AR activation. Thus, G-1 inhibits isoproterenol-induced increases in left ventricle (LV) pressure, heart rate, ectopic contractions, I Ca,L , LTCC phosphorylation, and total myocardial Ca 2+ signal, while the GPER inhibitor G-36 promotes ISO-induced Ca 2+ signal and LTCC phosphorylation ( 213 ). Speculatively, GPER may do so in part by interacting with β 1 AR or with A kinase-anchoring protein 5, thus inhibiting cAMP production ( 167 ).…”
Section: Calcium Entry Inhibition By Estrogenic Agonists and Estrogenmentioning
confidence: 99%
“…Reciprocality between estrogen signaling and Ca 2+ -dependent activities is becoming evident. Considering the impact of estrogen and its receptors on Ca 2+ signaling , E 2 , and in many cases, GPER exert inhibitory effects on many components of the CSM in cardiovascular tissues, from Ca 2+ store release and uptake ( 214 , 215 , 221 ) and Ca 2+ entry ( 199 , 201 210 , 212 , 213 ) to cytosolic Ca 2+ removal mechanisms ( 135 , 170 , 208 , 217 221 ). Considering the impact of Ca 2+ signaling on estrogen biology , both ERα and GPER are strongly regulated by direct Ca 2+ -dependent interactions with CaM.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Numerous studies have, in fact, shown that estrogens were able to increase calcium-regulated proteins [78,79], including ATPase and membrane channels in different cell types [80][81][82][83][84]. Therefore, ERs-mediated signaling can have profound implications in the regulation of cardiac contractile activity, physiologically under the control of ARs [85][86][87].…”
Section: Interplay Between Ers and β-Ars And Its Potential Therapeutic Valuementioning
confidence: 99%